Analisis Sistem Pengelolaan Air Asam Tambang Berbasis Fitoremediasi Tanaman Lokal dalam Green Supply Chain Management - Yelli Fitri, Yelli Fitri; Wahyuni , Sri; Leka, Emil Salim Kahmi (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Acid Mine Drainage (AMD) is one of the most serious environmental impacts of mining activities, especially coal mining. It is characterized by low pH and high concentrations of heavy metals such as Fe, Mn, and Cr. This study aims to analyze a phytoremediation-based AMD management system using local plants. The research methods include a literature review and system modeling using the IDEF0 approach to illustrate the AMD management flow. A SWOT analysis was also conducted. The results show that phytoremediation can reduce heavy metal content by more than 90% and raise the pH of the acidic water from below 4 to near neutral (pH 6–7) within a certain period. From an industrial engineering perspective, this system is efficient because it utilizes local resources, reduces operational costs compared to chemical methods, and supports Green Supply Chain Management (GSCM) based on circular economy principles. The integration of phytoremediation into the mining green supply chain provides added value in terms of environmental sustainability, regulatory compliance, and corporate image enhancement.